89.5k views
3 votes
2(x - 3) + 3 = 6x - 5.

User Ccpmark
by
4.3k points

2 Answers

3 votes

Answer:

x=-4

Explanation:

Distribute 2(x-3)= 2x-6 So, your new equation is 2x-6=6x-5. Then, you would subtract 2x from 6x so your new equation is -6=4x-5 then add 5 to both sides. so your new equation is -1=4x then you divide -1 from both sides and you'd get x=-4

User Thesis
by
5.2k points
1 vote

Answer:

Solution for 2(x-3)+3=6x-5 equation:

Simplifying

2(x + -3) + 3 = 6x + -5

Reorder the terms:

2(-3 + x) + 3 = 6x + -5

(-3 * 2 + x * 2) + 3 = 6x + -5

(-6 + 2x) + 3 = 6x + -5

Reorder the terms:

-6 + 3 + 2x = 6x + -5

Combine like terms: -6 + 3 = -3

-3 + 2x = 6x + -5

Reorder the terms:

-3 + 2x = -5 + 6x

Solving

-3 + 2x = -5 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.

-3 + 2x + -6x = -5 + 6x + -6x

Combine like terms: 2x + -6x = -4x

-3 + -4x = -5 + 6x + -6x

Combine like terms: 6x + -6x = 0

-3 + -4x = -5 + 0

-3 + -4x = -5

Add '3' to each side of the equation.

-3 + 3 + -4x = -5 + 3

Combine like terms: -3 + 3 = 0

0 + -4x = -5 + 3

-4x = -5 + 3

Combine like terms: -5 + 3 = -2

-4x = -2

Divide each side by '-4'.

x = 0.5

Simplifying

x = 0.5

Explanation:

User Irtaza
by
5.0k points